Upholding the Impartiality of Judges in Judicial Systems - Nurudin, Agus (Faculty of Law, Hasanuddin University, 2020)
Free and impartial justice is a characteristic and ideal of a constitutional State. In societies with a free and open judiciary system, individuals are permitted to challenge a judge's verdict, ability to remain impartial, and conduct. This article a doctrinal research with statute, comparative, and conceptual approaches. Meanwhile, data were analyzed descriptively, consisting of quotes. The results show that impartiality legal process (free from pressure, both physical and psychological and impartial) is a characteristic of a constitutional State. In the criminal justice system has received a full principle of free and impartial justice. At the lowest level, this principle in criminal justice is played by the judge as the core apparatus of judicial power, the principle of freedom and impartiality of judges in examining, hearing and deciding cases. The treatment in a crime must always be brought to the application of the principle of impartiality or treatment as referred in the principles of impartiality. Likewise, the principle of impartiality must not only be applied to suspects or defendants, it must be interpreted including the treatment of crown witnesses, victim witnesses and their families and also cannot be ignored about the existence of the community as legal subjects who have an interest in the implementation of public law.